A CASE OF NEUROFIBROMATOSIS TYPE 2 WITH UNUSUAL CLINICAL FEATURES. Issue Volume 14:Issues 1(2020) (2020) - Zarei, Mohamma; Hamzeloui, Parisa; Rooipoor, Ramak; Fard, Masoud Aghsaei
Abstract : Purpose: To report a case of a neurofibromatosis Type 2 with unusual clinical features. Methods: Observational clinical case report. Results: A 22-year-old woman was referred with bilateral blurred vision and macular "scars." Ocular examination revealed bilateral posterior subcapsular and cortical cataract, optic disk swelling, hyperpigmented macular lesions, epiretinal membrane, and macular temporal dragging. Spectral-domain optical coherence tomographic imaging showed bilateral epiretinal membranes, peripapillary nerve fiber layer thickening, and vitreoretinal tractional bands. In the right eye, focal choroidal excavation was noted at the site of the macular lesion. In fluorescein angiography, mild vascular leakage, capillary nonperfusion, and ground glass hyperfluorescence was seen in temporal periphery of the right eye. Brain imaging showed intracranial calcification and vestibular schwannoma, which was removed by a neurosurgeon. A clinical diagnosis of neurofibromatosis Type 2 was made. Conclusion: A case of neurofibromatosis Type 2 with some possibly novel or rare findings, namely, focal choroidal excavation, ash leaf spots, and intracranial calcifications was presented. Abstract : This case highlights the importance of complete systemic examination and history taking in diagnosing potentially life-threatening conditions in patients presenting with visual symptoms. Moreover, a case of neurofibromatosis Type 2 with some possibly novel or rare findings, namely, focal choroidal excavation, ash leaf spots, and intracranial calcifications was presented.